2017
DOI: 10.1002/cphc.201601370
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Valeric Acid Ketonization and Ketenization in Catalytic Pyrolysis on Nanosized SiO2, γ‐Al2O3, CeO2/SiO2, Al2O3/SiO2 and TiO2/SiO2

Abstract: Valeric acid is an important renewable platform chemical that can be produced efficiently from lignocellulosic biomass. Upgrading of valeric acid by catalytic pyrolysis has the potential to produce value added biofuels and chemicals on an industrial scale. Understanding the different mechanisms involved in the thermal transformations of valeric acid on the surface of nanometer-sized oxides is important for the development of efficient heterogeneously catalyzed pyrolytic conversion techniques. In this work, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 77 publications
(275 reference statements)
4
30
0
3
Order By: Relevance
“…The interaction between the metal atom and the carboxyl group can be attributed to four types: bidentate chelate or bidentate bridge coordination, monodentate coordination and ionic interaction [50,51]. For bidentate chelate structures the difference between ν as COO − and ν s COO − (∆=ν as COO − − ν s COO − ) is less than 110 cm −1 , for bidentate bridges structures ∆ ≈ 140-190 cm −1 , while monodentate structures and non-dissociated acids are characterized by the highest values of ∆ (∆ = νC=O-νC-O~200-320 cm −1 ) [51].…”
Section: Fourier Transform-infrared (Ft-ir) Spectroscopy Of Caffeic Amentioning
confidence: 99%
“…The interaction between the metal atom and the carboxyl group can be attributed to four types: bidentate chelate or bidentate bridge coordination, monodentate coordination and ionic interaction [50,51]. For bidentate chelate structures the difference between ν as COO − and ν s COO − (∆=ν as COO − − ν s COO − ) is less than 110 cm −1 , for bidentate bridges structures ∆ ≈ 140-190 cm −1 , while monodentate structures and non-dissociated acids are characterized by the highest values of ∆ (∆ = νC=O-νC-O~200-320 cm −1 ) [51].…”
Section: Fourier Transform-infrared (Ft-ir) Spectroscopy Of Caffeic Amentioning
confidence: 99%
“…Cinnamic acids on the silica surface transform into corresponding ketenes, vinyl-and acetylene-benzenes via three parallel pathways b, e and f: ketenization, decarboxylation, and decarbonylation, [51][52][53]; whereas over the nanoceria surface, only the decarboxylation (f) takes place [54]. A comparative study [41] of pyrolytic decomposition of valeric acid over SiO 2 , Al 2 O 3 , CeO 2 /SiO 2 , Al 2 O 3 /SiO 2 , and TiO 2 /SiO 2 catalysts showed that propylketene forms on the surfaces of all these oxides except for CeO 2 /SiO 2 . The formation of both ketene and ketone was observed on the surface of Al 2 O 3 .…”
Section: Kinetic Studymentioning
confidence: 99%
“…Rather the loss of the CO 2 or the formation of a new C-C bond are the likely rate-determining steps [26,32,33,36]. Despite the enormous efforts spent on the establishment of the mechanism of this reaction, kinetic studies, isotope effect studies [26,27,36], quantum chemical calculations [30][31][32][33]36], studies of cross-ketonization reactions [28,30,33,38], 13 C/ 12 C exchange studies [34], H/D exchange studies on the catalyst surfaces [28,29,39], experiments with 13 C-labeled acetic acids [28,33,34], Fourier Transform Infrared Spectroscopy FT-IR studies [36,37,[39][40][41], etc., the question of establishing the full details of the ketonization reaction mechanism is still not completely closed [39]. However, linear free energy relationships (LFERs) have never been applied to study of the mechanism of ketonization.…”
Section: Kinetic Studymentioning
confidence: 99%
See 2 more Smart Citations